High-Quality Perovskite CH(3)NH(3)PbI(3) Thin Films for Solar Cells Prepared by Single-Source Thermal Evaporation Combined with Solvent Treatment - Peng, Huanxin (Materials (Basel), 2019)
In this work, solvent annealing process for CH(3)NH(3)PbI(3) thin film prepared by single source evaporation was reported. Characterized by the scanning electron microscope (SEM), X-ray diffractometer (XRD), energy dispersive spectroscope (EDS), ultraviolet-visible (UV) spectrophotometer, and the photoluminescence (PL) spectrometer, our method ensured higher quality film with crystallinity, composition, well-defined grain structure, and reproducibility. The optimized solar cell device based on the structure of ITO/PEDOT:PSS/CH(3)NH(3)PbI(3)/PCBM/Ag achieved better performance in power conversion efficiency from 2.64% to 9.92%, providing an effective method to optimize the quality of perovskite film for solar cell application.